Systematic genetic analysis of pediatric patients with autoinflammatory diseases - Poker, Yvonne; von Hardenberg, Sandra; Hofmann, Winfried; Tang, Ming; Baumann, Ulrich; Schwerk, Nicolaus; Wetzke, Martin; Lindenthal, Viola; Auber, Bernd; Schlegelberger, Brigitte; Ott, Hagen; von Bismarck, Philipp; et al. (Frontiers in Genetics, 2023)
Monogenic autoinflammatory diseases (AID) encompass a growing group of inborn errors of the innate immune system causing unprovoked or exaggerated systemic inflammation. Diagnosis of monogenic AID requires an accurate description of the patients´ phenotype, and the identification of highly penetrant genetic variants in single genes is pivotal. We performed whole exome sequencing (WES) of 125 pediatric patients with suspected monogenic AID in a routine genetic diagnostic setting. Datasets were analyzed in a step-wise approach to identify the most feasible diagnostic strategy. First, we analyzed a virtual gene panel including 13 genes associated with known AID and, if no genetic diagnosis was established, we then analyzed a virtual panel including 542 genes published by the International Union of Immunological Societies associated including all known inborn error of immunity (IEI). Subsequently, WES data was analyzed without pre-filtering for known AID/IEI genes. Analyzing 13 genes yielded a definite diagnosis in 16.0% (n=20). The diagnostic yield was increased by analyzing 542 genes to 20.8% (n=26). Importantly, expanding the analysis to WES data did not increase the diagnostic yield in our cohort, neither in single WES analysis, nor in trio-WES analysis. The study highlights that analyzing virtual gene panels based on WES that include the majority of known genes causing AID or differential diagnosis can rapidly confirm the diagnosis for a large number of pediatric patients. WES data or trio-WES data analysis as a first-tier diagnostic analysis in patients with suspected monogenic AID is of limited benefit.